Dicranostigma platycarpum, a new synonym of Dicranostigma erectum (Papaveraceae) - Hongjin, Dong; Chunlei, Xiang (Phytotaxa, 2015)
Dicranostigma Hooker f. & Thomson (1855: 255), a genus of three species in Papaveraceae (1789: 235), disjunctively distributed in the Loess Plateau and the Hengduan Mountains in China and the neighboring Himalayan Mountains. Species in Dicranostigma are typically yellow-lactiferous herbs with four yellow petals, numerous stamens, one-loculed ovary, terete or linear capsule, and tessellate seeds. According to Zhang & Grey-Wilson (2008), there are three species from China, i.e., D. lactucoides Hooker f. & Thomson (1855: 255), D. leptopodum (Maximowicz) Fedde (1905: 45), and D. platycarpum C.Y. Wu & H. Chuang (1985: 87), and the latter two are endemic to China.